2017
DOI: 10.1111/1467-8578.12187
|View full text |Cite
|
Sign up to set email alerts
|

A capability approach for online primary and secondary students with disabilities

Abstract: A capability approach was used to identify and synthesise research studies about online students with disabilities in primary and secondary school (aged five to 18 years) in an attempt to describe the experience from an empirical perspective. A capability approach is intended to maximise agency and can be used to describe the extent to which individuals are able to use limited resources to build a satisfying and enjoyable life. In this analysis, a derived capability set was used to narrow the larger body of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Research on online schooling and blended learning (combinations of in-person and online schooling) is still at an emerging stage; however, such approaches are increasingly used with children with chronic illness ( Coy, 2014 ; Stella & Corry, 2017 ). It has been suggested that children with chronic illness may benefit from the individualized pacing and freedom to make mistakes without peers around that is uniquely available with online formats ( Stella & Corry, 2017 ). It is also expected that online schooling may promote metacognitive skills, such as autonomy and responsibility ( Terras, Leggio, & Phillips, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research on online schooling and blended learning (combinations of in-person and online schooling) is still at an emerging stage; however, such approaches are increasingly used with children with chronic illness ( Coy, 2014 ; Stella & Corry, 2017 ). It has been suggested that children with chronic illness may benefit from the individualized pacing and freedom to make mistakes without peers around that is uniquely available with online formats ( Stella & Corry, 2017 ). It is also expected that online schooling may promote metacognitive skills, such as autonomy and responsibility ( Terras, Leggio, & Phillips, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…While we explored the application of the capability approach in the use and protection of ICTs, we found literature that points to its shortcomings. Stella and Corry [51] point to the vagueness of the capability approach. Gasper [52] highlights difficulties in operationalising the capability approach also citing its vagueness.…”
Section: Q3: Criticismsmentioning
confidence: 99%